Participatory mapping in low-resource settings: Three novel methods used to engage Kenyan youth and other community members in community-based HIV prevention research - Green, Eric P. (Glob Public Health, 2016)
Understanding the link between health and place can strengthen the design of health interventions, particularly in the context of HIV prevention. Individuals who might one day participate in such interventions—including youth—may further improve the design if engaged in a meaningful way in the formative research process. Increasingly, participatory mapping methods are being used to achieve both aims. We describe the development of three innovative mapping methods for engaging youth in formative community-based research: ‘dot map’ focus groups, geocaching games, and satellite imagery assisted daily activity logs. We demonstrate that these methods are feasible and acceptable in a low-resource, rural African setting. The discussion outlines the merits of each method and considers possible limitations.